Metropolitan Region: Evolution of Thinking and Spatial Organization for the Case of New York Metropolitan Area - Яценко, Борис Павлович; Денисенко, Олена Олександрівна (Київський національний університет імені Тараса Шевченка, 2021)
Aim. The article is aimed to show the evolution of approaches and current thinking on metropolitan regions in the context of world urbanization; to analyze the main tendencies of New York metropolitan area development – one of the biggest metropolitan regions in the world with a core in a global city; basing on the case of New York, to illustrate the evolution of the methodology for metropolitan region delineation, its planning and spatial development in long-term perspective. Methodology. The methodology is based on a long-term analysis of the dynamics of New York city as well as spatial organization of the metropolitan region from the viewpoint of the evolution of approaches for delineation of the urbanized areas in the US and spatial planning perspectives, basing on several generations of New York metropolitan area regional plans. Results. The article reflects the evolution of ideas and basic concepts of metropolitan regions development as spatial entities. Basing on the US experience in the methodology of urban areas delineation, the main changes over recent decades and their relation to urbanization processes are reflected, in particular the role of low-density corridors, population density and housing density as criteria for urban areas identification is analyzed. This experience can be used to develop a methodology for identifying metropolitan regions in Ukraine, making delineation process and providing more balanced governance policy for these regions. Using the example of New York, the article shows the need to constantly update and adapt governance and planning policies in such regions, which is reflected in changes of managing growth, now mostly focusing on reducing segregation, preventing climate change, enhancing institutional transformations and strengthening the role of spatial planning. Novelty. Revealing the experience of metropolitan regions delineation, challenges for their spatial development and planning strategy for the case of New York metropolitan area, the article reflects actual methodological approaches to metropolitan regions delineation, making governance policy and spatial planning that can be adapted in Ukraine. Among the key proposed changes aimed at strengthening the sustainable development of such regions in Ukraine - development the methodology for their delineation, elaboration of metropolitan region development strategy and spatial planning for the whole region.

Мета – розкрити еволюцію підходів до визначення та сучасні уявлення про метрополітенські регіони на фоні урбанізаційних процесів у світі, а також тенденцій розвитку такого регіону для випадку Нью-Йорка - центру одного з найбільших метрополітенських регіонів з ядром у глобальному місті; на прикладі регіону відобразити зміни методичних підходів до ідентифікації меж та планування його просторового розвитку у довгостроковій перспективі. Методика базується на довгостроковому аналізі динаміки розвитку міста, а також просторової організації метрополітенського регіону крізь призму еволюції підходів до визначення урбанізованих територій у США та планування розвитку регіону, спираючись при цьому на декілька поколінь регіональних планів, розроблених для метрополітенського регіону Нью-Йорка. Результати. У статті відображено еволюцію уявлень та основні концепції розвитку метрополітенських регіонів як просторових утворень. Спираючись на досвід США щодо методики визначення урбанізованих територій, відображено зміни методичних підходів протягом останніх десятиліть та їх зв’язок з урбанізаційними процесами, зокрема показано вплив критеріїв величини розривів між житловою забудовою, щільності населення та щільності житлових приміщень на визначення урбанізованих територій. Дані критерії можуть бути використані для розроблення методики ідентифікації метрополісних регіонів в Україні, коректного визначення їх меж та з метою становлення зваженої політики розвитку цих регіонів. На прикладі Нью-Йорка у статті показано необхідність постійного оновлення та адаптації політики управління та планування такими регіонами, що виявляється у зміні моделі росту, фокусами якої є зменшення сегрегації, попередження кліматичних змін, інституційні трансформації та посилення ролі просторового планування. Наукова новизна – розкриваючи досвід визначення меж метрополітенських регіонів, викликів для їх просторового розвитку та принципи політики планування на прикладі метрополітенського регіону Нью Йорка, стаття відображає актуальні методичні підходи до визначення таких регіонів, становлення політики їх розвитку та планування, що можуть бути адаптовані в Україні. Серед ключових пропонованих змін, що покликані посилити збалансованість розвитку таких утворень в Україні – розроблення методики визначення меж таких регіонів, формування спільної стратегії розвитку та просторового планування.
Метрополітенський регіон: еволюція підходів та особливості просторової організації на прикладі Нью-Йорка, США
Keywords: метрополітенський регіон; урбанізовані території; просторове планування; Нью-Йорк; регіональний план; metropolitan region; urbanized areas; spatial planning; New York; regional plan